Decentralized File Sharing Infrastructure with IPFS for Censorship Resistance in Blockchain Ecosystems - Nesti Anggraini Santoso; Palma Juanta; Sabda Maulana; Kerimbekov Toktar; Aulia Khanza (Blockchain Frontier Technology, 2025)
Traditional file sharing systems that rely on centralized servers face various challenges. problems such as vulnerability to censorship, blocking, and server failures.This research focuses on the need for file sharing technology that is more secure, censorship-resistant, and does not rely on a single central authority. Challenge the main challenge in developing a new file sharing system is how to overcome the limitations of network scale, slow access speed, and lack of incentives for node providers. Research purposes this is to analyze the role of the InterPlanetary File System (IPFS) in building a censorship-resistant file sharing infrastructure and evaluate its benefits and constraints compared to conventional file sharing systems. Findings from the literature study show that IPFS has advantages in data decentralization, increasing information availability, and strengthening resistance to censorship. Research results also revealed that although IPFS is able to overcome many weaknesses of traditional systems, further development is still needed in terms of network efficiency and user incentives. In conclusion, IPFS has great potential to become the main foundation in a future digital ecosystem that is more open, secure, and free from third-party intervention.